2022
DOI: 10.1111/birt.12666
|View full text |Cite
|
Sign up to set email alerts
|

Developing a woman‐centered, inclusive definition of positive childbirth experiences: A discussion paper

Abstract: Introduction: A positive childbirth experience promotes women's health, both during and beyond the perinatal period. Understanding what constitutes a positive childbirth experience is thus critical to providing high-quality maternity care. Currently, there is no clear, inclusive, woman-centered definition of a positive childbirth experience to guide practice, education, and research. Aim: To formulate an inclusive woman-centered definition of a positive childbirth experience. Methods: A six-step process was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…92 As the birth narrative and phenomenological accounts on birth have shown, women in labour are ideally supported by the birth attendants and their significant others in such a way that the limit situation during labour is not experienced as an existentially threatening loss of agency, as alienation and reification, but as a process in which she feels safe due to the support she receives, and in which she experiences an empowering 'I can' accompanied by positive feelings such as joy, satisfaction, or pride. 60 A positive birth experience depends on whether the woman giving birth feels respected, supported and protected by the birth attendants or whether she feels disregarded, patronised and left alone. 15,57 Thus, the actual task of the obstetricians and midwives does not (only) lie in the artful supervision of birth, but 'in the accompanying and caring relationship formation of an existentially significant situation'.…”
Section: Applying Care Ethics To Intrapartum Carementioning
confidence: 99%
See 1 more Smart Citation
“…92 As the birth narrative and phenomenological accounts on birth have shown, women in labour are ideally supported by the birth attendants and their significant others in such a way that the limit situation during labour is not experienced as an existentially threatening loss of agency, as alienation and reification, but as a process in which she feels safe due to the support she receives, and in which she experiences an empowering 'I can' accompanied by positive feelings such as joy, satisfaction, or pride. 60 A positive birth experience depends on whether the woman giving birth feels respected, supported and protected by the birth attendants or whether she feels disregarded, patronised and left alone. 15,57 Thus, the actual task of the obstetricians and midwives does not (only) lie in the artful supervision of birth, but 'in the accompanying and caring relationship formation of an existentially significant situation'.…”
Section: Applying Care Ethics To Intrapartum Carementioning
confidence: 99%
“…50 (p. 33) Like Heyes’ account, Tömmel's narration reads like the perfect illustration of a recent definition of positive birthing experiences. 60 Although Heyes, Tömmel or the woman quoted by Lundgren might have felt ‘becoming possessed’, 29 (p. 162) too, the transformative experience they underwent was rather sublime than terrifying, empowering instead of paralysing, leading to feelings of joy and connection instead of estrangement. Despite being radically different from everyday experiences in many ways, Trigg's 41 conclusion ‘that the affective tonality of childbirth is best captured as a form of strangeness’ seems to be too one-sided to do justice to the diverse experiences of different women.…”
Section: Narrative Accounts Of Birthing Experiencesmentioning
confidence: 99%
“…This, in turn, predicts negative outcomes for both mother and child 3,4 . However, there is no consensus regarding the precise dimensions that engender positive birth experiences 5‐7 . In this paper, we argue that Basic Psychological Needs Theory, an existing framework, provides an optimal way to organize the vast literature on this topic.…”
Section: Introductionmentioning
confidence: 98%
“…summarized birth satisfaction as coming from internal factors (confidence and preparedness; feeling in control) and external factors (supportive relationships with caregivers, being seen and heard, and caregiver providing adequate information/guidance). Recently, Leinweber et al., 6 using a literature review and feedback from birth experts, defined a positive childbirth this way: “A woman's experience of interactions and events directly related to childbirth that made her feel supported, in control, safe, and respected; a positive childbirth can make women feel joy, confident, and/or accomplished and may have short and/or long‐term positive impacts on a woman's psychosocial well‐being” (p. 364).…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have identified various elements related to childbirth experiences, such as the mother's individual factors (parity, experiences of female support during childbirth, cultural background and expectations of childbirth); interpersonal factors related to companions and healthcare professionals attending the birth, and factors related to the sense of control and perceived safety, both physically and emotionally (Chabbert et al., 2021; Leinweber et al., 2022; Vedeler et al., 2022).…”
Section: Introductionmentioning
confidence: 99%